Strategi Peningkatan Nilai Tambah dan Pendapatan Nelayan Tangkap Berbasis Tepung Ikan untuk Meraih Potensi Pasar Pakan Ternak Unggas sebagai - Monoarfa, Hilda; Chalil, .; Taqwa, Edhi (Universitas Brawijaya, Indonesia, 2015)
The short-term goal of the study is to formulate fishermen 's revenue value - added strategy in fish flour productions in order to reach potential poultry food market as an effort to reduce imported dependence of fish flour in Indonsia. The long-term goal of the study refers to the MP3EI is implementation of value-added enhancements strategy for fishermen through programs and activities in order to fulfill the market demand in order to increase the income and welfare of fishermen in Tojo Una-Una, Central Sulawesi of Indonesia. The sample is limited to fishermen who have fishing gear boats and motor boats. The location of this study is in the Ampana City District ( Dondo village and Labuan village), Tojo District (Uekuli village and Tayawa village), and Una-Una District (Wakai village, Tanjung Pude, Una-Una village). The method used descriptive and SWOT analysis. The results indicate that the successfulness of fishermen's revenue value-added strategy through fish flour productions to reach poultry food potential market is influenced by some steps: 1) to increase production through the improvement of fishing gear; (2) to build solid fishing cooperatives and marketing institutions (TPI); (3) to enhance access to capital through bankinginstitutions; (4) to develop marine and fisheries-based entrepreneurship; (5) to provide a comprehensive, focused, and well-managed mentoring program; and (6) to monitorand evaluate the development and sustainability of the program.